Obstetrical and epidemiological factors influence the severity of anal incontinence after obstetric anal sphincter injury - France Joris; Irene Hoesli; Andre Kind; Jean Jacques Ries; Tilemachos Kavvadias (BMC, 2019)
Abstract Background Obstetric anal sphincter injury (OASI) is one of the most severe obstetrical complications. Although risk factors for OASI have been identified, little is known about various parameters that can influence symptoms' severity. The aim of this study is to explore whether obstetrical and epidemiological factors can have an effect on the severity of symptoms after OASI. Methods 11.483 deliveries between January 2010 and December 2014 were reviewed, and data from 88 women with OASI are presented. Results The only statistically significant differences between symptomatic and asymptomatic women were age (p = 0.02), body mass index (p = 0.04) and the use of forceps (p = 0.04). Women with more severe symptoms were more likely to have received oxytocin during the second stage of labor (p = 0.03) and had shorter delivery to follow-up interval (p = 0.008). Conclusions Modifiable factors such as use of forceps and oxytocin should be taken into consideration in clinical practice.